Targeting a coatomer protein complex-I gene via RNA interference results in effective lethality in the pollen beetle Brassicogethes aeneus - Jonathan Willow; Silva Sulg; Clauvis Nji Tizi Taning; Ana Isabel Silva; Olivier Christiaens; Riina Kaasik; Katterinne Prentice; Gabor L. Lövei; Guy Smagghe; Eve Veromann (Journal of Pest Science, 2021)
The pollen beetle Brassicogethes aeneus is a serious pest of oilseed rape ( Brassica napus ) in Europe. Management of this pest has grown difficult due to B. aeneus ’s development of resistance to pyrethroid insecticides, as well as the pressure to establish control strategies that minimise the impact on nontarget organisms. RNA interference represents a nucleotide sequence-based, and thus potentially species-specific, approach to agricultural pest control. The present study examined the efficacy of targeting the coatomer gene coatomer subunit alpha ( αCOP ), via both microinjection and dietary exposure to exogenous complementary dsRNA, on αCOP -silencing and subsequent mortality in B. aeneus . Beetles injected with dsRNA targeting αCOP (at 0.14 µg/mg) showed 88% and 100% mortality at 6 and 10 days post-injection, respectively; where by the same time after dietary exposure, 43%–89% mortality was observed in the 3 µg dsRNA/µL treatment, though the effect was concentration-dependent. Thus, the effect was significant for both delivery routes. In working towards RNA-based management of B. aeneus , future studies should include αCOP as a target of interest.